Morphometric changes and sex steroid levels during the annual reproductive cycle of the Lusitanian toadfish, Halobatrachus didactylus - Modesto, Teresa (2012)
The Lusitanian toadfish has group synchronous oocytes, which grow from November until June–July when they are released probably as a single batch. Blood plasma levels of estradiol-17b (E2) and testosterone (T) increase during vitellogenesis and drop rapidly during final maturation and ovulation, when 17,20b, 21-trihydroxy-4-pregnen-3-one (17,20b,21-P) levels increase. The male reproductive apparatus is composed of paired testes and multichambered accessory glands, which secrete mucosubstances and are connected to the spermatic duct. Changes in the gonadosomatic index of males paralleled the females but started to drop slightly earlier. The swimbladder and accessory glands also underwent important seasonal changes in weight reaching a maximum at spawning. T, 11-ketotestosterone (11-KT) and 17,20a-dihydroxy-4-pregnen-3-one (17,20a-P) were generally low except for a sharp peak in June. 17,20b,21-P also peaked in June and then declined slowly. 17,20b-dihydroxy-4-pregnen-3-one (17,20a-P) was undetectable in males and females. As with other species of the family two types of males were identified: type I males with smaller testes (ca. 7-fold) and larger accessory glands (ca. 3-fold) and swimbladders than type II. Type I males also had significantly higher (ca. 6- fold) 11-KT levels than type II males. This suggests a role for 11-KT in the development of structures important for reproductive behaviour.